Flavin Oxidase-Induced ROS Generation Modulates PKC Biphasic Effect of Resveratrol on Endothelial Cell Survival - Anna Maria Posadino (13917535) (2019)
Background: Dietary intake of natural antioxidants is thought to impart protection against oxidative-associated cardiovascular diseases. Despite many in vivo studies and clinical trials, this issue has not been conclusively resolved. Resveratrol (RES) is one of the most extensively studied dietary polyphenolic antioxidants. Paradoxically, we have previously demonstrated that high RES concentrations exert a pro-oxidant effect eventually elevating ROS levels leading to cell death. Here, we further elucidate the molecular determinants underpinning RES-induced oxidative cell death. Methods: Using human umbilical vein endothelial cells (HUVECs), the effect of increasing concentrations of RES on DNA synthesis and apoptosis was studied. In addition, mRNA and protein levels of cell survival or apoptosis genes, as well as protein kinase C (PKC) activity were determined. Results: While high concentrations of RES reduce PKC activity, inhibit DNA synthesis and induce apoptosis, low RES concentrations elicit an opposite effect. This biphasic concentration-dependent effect (BCDE) of RES on PKC activity is mirrored at the molecular level. Indeed, high RES concentrations upregulate the proapoptotic Bax, while downregulating the antiapoptotic Bcl-2, at both mRNA and protein levels. Similarly, high RES concentrations downregulate the cell cycle progression genes, c-myc, ornithine decarboxylase (ODC) and cyclin D1 protein levels, while low RES concentrations display an increasing trend. The BCDE of RES on PKC activity is abrogated by the ROS scavenger Tempol, indicating that this enzyme acts downstream of the RES-elicited ROS signaling. The RES-induced BCDE on HUVEC cell cycle machinery was also blunted by the flavin inhibitor diphenyleneiodonium (DPI), implicating flavin oxidase-generated ROS as the mechanistic link in the cellular response to different RES concentrations. Finally, PKC inhibition abrogates the BCDE elicited by RES on both cell cycle progression and pro-apoptotic gene expression in HUVECs, mechanistically implicating PKC in the cellular response to different RES concentrations. Conclusions: Our results provide new molecular insight into the impact of RES on endothelial function/dysfunction, further confirming that obtaining an optimal benefit of RES is concentration-dependent. Importantly, the BCDE of RES could explain why other studies failed to establish the cardio-protective effects mediated by natural antioxidants, thus providing a guide for future investigation looking at cardio-protection by natural antioxidants. Other Information Published in: Biomolecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/biom9060209